Trauma and coping in battling the COVID-19 pandemic among Malaysian healthcare workers - Mohd Noor, Norhafizah; Ariffin, Ahmad Azuhairi; Silim, Umi Adzlin; Md Said, Salmiah (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2023)
Introduction: Prolonged COVID-19 pandemic with high morbidity and mortality may cause traumatic events to Healthcare Workers (HCW), resulting in Post-Traumatic Stress Disorder (PTSD) symptoms. Hence, this study aims to determine the prevalence of PTSD symptoms and its association with coping strategies among HCW in managing COVID-19 pandemic at Klang Valley Public Hospitals in Malaysia. Methods: A cross-sectional study with total of 424 eligible respondents were recruited through stratified random sampling. Data was collected from 6th May until 6th June 2021 using a self-administered online questionnaire adopted from MPCL-5 and Brief COPE instruments. IBM Statistical Package for Social Sciences Version 26 was used to analyse data. Result: 25 of the respondents demonstrated PTSD symptoms. Respondents who are single (aOR=3.319, 95 CI: 1.912, 5.762, p-value < 0.001), behavioural disengagement (aOR= 7.262, 95 CI: 1.973, 26.723, p-value =0.003), humour (aOR= 5.303, 95 CI: 1.754, 16.039, p-value =0.003), venting emotion (aOR= 3.287, 95 CI: 1.521, 7.105, p-value =0.002) and less planning (aOR= 2.006, 95 CI:1.154, 3.487 p-value =0.014) are significant predictors for PTSD symptoms. Conclusion: One in four HCW managing COVID-19 in Klang Valley public hospitals experienced PTSD symptoms. Therefore, urgent interventional program targeting HCW who are single with history of positive COVID-19 is beneficial to prevent PTSD. Maladaptive coping strategies like self-blaming, venting emotion, humour and behavioural disengagement should be replaced with more adaptive coping strategies like planning, self-compassion, self-care and self-reflection.